A framework to assess the valuation techniques for new technology-based firms: a case in an emerging market. Issue 3 (2nd October 2022) - Dastkhan, Hossein
ABSTRACT: Valuation of new technology-based firms and startups is one of the main concerns of these Firms. The need to expand financial resources and evaluate the potential income of these firms increases the importance of the valuation of these firms for entrepreneurs and investors. In this paper, we represent a comprehensive framework to assess the strengths and the weaknesses of the valuation methods in NTBFs with a focus on the factors in the emerging markets. For this purpose, different valuation methods and their related criteria for NTBFs are extracted and evaluated by experts in terms of applicability and Sufficiency. We categorized the existing valuation methods to 4 different groups: " asset valuation methods ", " intellectual property valuation methods", " technology valuation methods ", and " startups valuation methods ". Then, the importance of each criterion is determined using the analytical hierarchical process method. Finally, we used fuzzy TOPSIS to prioritize each category of valuation methods and identify their strengths and weaknesses. The results indicate which sets of valuation methods are the more preferred method for Iranian entrepreneurs and investors to evaluate different kinds of NTBFs. Besides, the results of the model on different criteria proposed different suggestions to improve the existing valuation methods.